STUDI BIOAKTIVITAS DAN ISOLASI SENYAWA BIOAKTIF TUMBUHAN Euphorbia tirucalli L. (EUPHORBIACEAE) SEBAGAI INSEKTISIDA BOTANI ALTERNATIF - Moh. Hibban Toana; Burhanuddin Nasir (Universitas Tadulako, 2010)
The objective of this research were to identify the groups of secondary metabolites which act as bioactive in E. tirucalli plants, to isolate and determine those compounds, and to determine the bioactivity and toxicity of each purified compound. The research results showed that the extraction using ethanol solvent produced more extract yield of 6.6% (23.11 g) compared with acetone solvent (1.74% or equal to 6.08 g), while hexane solvent resulted in extract yield of 0.05% (1.74 g). Isolation and purification of E. tirucalli leaf extract by ethanol solvent produced 5 metabolites compounds including alkaloid, flavonoid, triterpenoid, and hydroquinone. While the acetone solvent produced 6 metabolites compounds including alkaloid, flavonoid, steroid, triterpenoid and hydroquinone. E. tirucalli leaf extracted by acetone solvent has highest toxicity, in which concentration of 2% was able to cause 50% mortality of P xylostella insects tested, compared with the ethanol solvent at a concentration of 3%.